Familiarity and Use of Digital Resources by the Library Users in Agriculture Universities of Himachal Pradesh: A Study - Mittal, Arvind; Sharma, B. K. (Indian Journal of Information Sources and Services, 2013)
With the application of ICT, library services have totally been changed. Library collection changed from traditional hard copy to digital or electronic form. Today users use the digital/e-resources like e-journals, databases, e-thesis, e-books etc. according to their needs and demands. So, libraries of agricultural university of Himachal Pradesh are also providing these services to their users according to their demands. Internet plays a vital role in providing digital resources to the users. It is essential that every user who wants to take the benefits of digital/e-resources should be familiar with the internet. Internet is a linker between the library and its users, which connects the users with the library resources. The present study is an attempt to analyses the user’s familiarity with the digital resources, its use by them and also examines the problems faced by them in using these resources in agricultural universities of Himachal Pradesh.